Vaccine implementation factors affecting maternal tetanus immunization in low- and middle-income countries: Results of the Maternal Immunization and Antenatal Care Situational Analysis (MIACSA) project - Giles, M.L. (Vaccine, 2020)
OBJECTIVES: To examine the characteristics of existing maternal tetanus immunization programmes for pregnant women in low- and middle-income countries (LMICs) and to identify and understand the challenges, barriers and facilitators associated with maternal vaccine service delivery that may impact the introduction and implementation of new maternal vaccines in the future. DESIGN: A mixed methods, cross sectional study with four data collection phases including a desk review, online survey, telephone and face-to-face interviews and in country visits. SETTING: LMICs. RESULTS: The majority of countries (84/95; 88%) had a maternal tetanus immunization policy. Countries with high protection at birth (PAB) were more likely to report tetanus toxoid-containing vaccine (TTCV) coverage targets > 90%. Less than half the countries included in this study had a TTCV coverage target of > 90%. Procurement and distribution of TTCV was nearly always the responsibility of the Expanded Programme on Immunization (EPI), however planning and management of maternal immunization was often shared between EPI and Maternal, Newborn and Child Health (MNCH) programmes. Receipt of TTCV at the same time as the antenatal care visit correlated with high PAB. Most countries (81/95; 85%) had an immunization safety surveillance system in place although only 11% could differentiate an adverse event following immunization (AEFI) in pregnant and non-pregnant women. CONCLUSIONS: Recommendations arising from the MIACSA project to strengthen existing services currently delivering maternal tetanus immunization in LMICs include establishing and maintaining vaccination targets, clearly defining responsibilities and fostering collaborations between EPI and MNCH, investing in strengthening the health workforce, improving the design and use of existing record keeping for immunization, adjusting current AEFI reporting to differentiate pregnant women and endeavoring to integrate the provision of TTCV within ANC services where appropriate.